Demographic and clinical characteristics of hospitalized children with suspected and laboratory-confirmed COVID-19 during the six waves of SARS-CoV-2 infection in northern Iran a retrospective cohort study - Mohammadi, Mohsen; Hashemi, Erfan; Shirafkan, Hoda; Sadeghi, Farzin; Yahyapour, Yousef (Frontiers in Pediatrics, 2024)
Northern Iran is one of the regions of the country most affected by COVID-19. The aim of the current study was to examine the demographics, clinical characteristics, and outcomes of suspected and laboratory-confirmed patients <18 years of age hospitalized over two years (during six waves of SARS-CoV-2). This retrospective cohort study examined hospitalized patients with suspected SARS-CoV-2 infection in Babol, northern Iran. The study included patients <18 years of age admitted to a pediatric referral hospital from March 7, 2020 to March 20, 2022. Epidemiological and demographic characteristics, real-time PCR cycle threshold (Ct), clinical data and COVID-19 results were analyzed in the hospitalized patients. Totally, 2731 patients with suspected COVID-19 were examined from March 2020 to 2022, with a mean age of 4.6 years, and were male (54.3%). Most suspected cases occurred during the fifth (Delta) and sixth (Omicron) relapse (30% and 20%. Among them, 461 patients had comorbidities, with brain and neurological diseases (BND), malignancies and hematopoietic and blood disorders (HBDs) being the most common (6.7%, 2.6% and 2.1%, respectively). Real-time RT-PCR showed that 391 patients were positive. The mean age of the positive patients was 5.2 years. Most positive cases were in the fifth wave (30.9%), male (53.7%) and 1-5 years old (49.1%). BND (9.5%) and cardiovascular diseases (CVD) (4.3%) were common underlying conditions. A higher viral load was most common in the fifth wave. Moreover, 8.7% of ICU admissions and 2.4% of deaths were due to a Ct score of 9-20. Most deaths occurred in the 1-5 age group and were associated with BND. More deaths occurred in women (73.9% overall, 71.4% real-time RT-PCR -positive), and the highest mortality was in the fifth wave. The risk ratio of mortality was higher in children with kidney disease (KD) and BND.There were 27 ICU admissions (6.9%) and seven deaths (1.8%). The current study also revealed that children of any age can be susceptible to SARS-CoV-2 infection, while children aged 1-5 years are more susceptible to COVID-19. The Delta variant is associated with higher rates of hospitalization and ICU admission, and the presence of BND is associated with higher mortality.